2007
DOI: 10.1158/0008-5472.can-06-0610
|View full text |Cite
|
Sign up to set email alerts
|

Credentialing Preclinical Pediatric Xenograft Models Using Gene Expression and Tissue Microarray Analysis

Abstract: Human tumor xenografts have been used extensively for rapid screening of the efficacy of anticancer drugs for the past 35 years. The selection of appropriate xenograft models for drug testing has been largely empirical and has not incorporated a similarity to the tumor type of origin at the molecular level. This study is the first comprehensive analysis of the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 24 publications
4
88
0
Order By: Relevance
“…When a model anti-endosialin-toxin conjugate was tested in the endosialin-positive SK-N-AS cell line and in the endosialin-negative HT-1080 fibrosarcoma cell line, the results showed that antigen-specific growth inhibition could be achieved in vitro via internalization of anti-endosialin (11). All 10 human neuroblastoma cell lines studied, both MYCN-amplified and non-MYCN-amplified, have been independently confirmed to be neuroblastoma cell lines using multiple mRNA and protein markers and clustering analysis (24). The presence of endosialin in MYCN-amplified lines is in accordance with the reported advanced clinical stage of some of the neuroblastoma lines.…”
Section: Discussionsupporting
confidence: 63%
“…When a model anti-endosialin-toxin conjugate was tested in the endosialin-positive SK-N-AS cell line and in the endosialin-negative HT-1080 fibrosarcoma cell line, the results showed that antigen-specific growth inhibition could be achieved in vitro via internalization of anti-endosialin (11). All 10 human neuroblastoma cell lines studied, both MYCN-amplified and non-MYCN-amplified, have been independently confirmed to be neuroblastoma cell lines using multiple mRNA and protein markers and clustering analysis (24). The presence of endosialin in MYCN-amplified lines is in accordance with the reported advanced clinical stage of some of the neuroblastoma lines.…”
Section: Discussionsupporting
confidence: 63%
“…With a consortium of laboratories in the United States and abroad, the program is able to quickly screen a large number of agents using in vitro and in vivo models. (65,(69)(70)(71) The in vitro models are cell lines, with the in vivo models typically human patient-derived tumors grown as heterotopic xenografts in severe combined immunodeficiency mice. Although osteosarcoma can be grown in orthotopic as well as heterotopic sites, the heterotopic site permits frequent tumor size measurements using a caliper, which is feasible and cost-effective.…”
Section: Preclinical Screeningmentioning
confidence: 99%
“…This program has generated a large amount of data, including characterizations of the model systems, that has rapidly been published or made available through Web-based applications (http://home.ccr.cancer.gov/oncology/oncogenomics/). (65,(69)(70)(71) Canine Models…”
Section: Preclinical Screeningmentioning
confidence: 99%
“…Current genomewide molecular-profiling studies indicate the retention of molecular characteristics that define tumor type. The recent study by Whiteford and colleagues 12 demonstrates that, by unsupervised clustering analysis of cDNA-expression profiles, xenografts derived from a histology can cluster accurately with their human counterparts. Similarly, direct comparison of patient tumor biopsy tissue with early-passage xenografts demonstrates high concordance in gene expression and even greater similarity in genomic alterations when tumors are propagated in mice.…”
Section: Introductionmentioning
confidence: 99%